The english rendering quality of al-hikmah, al-haqq, al-hajj, haitsu in surah al Baqarah by Mufti Taqi Usmani and Muhsin Khan & Hilali : comparative study - Aceng Bahrudin (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
wt,1./ws.c.1